Controllable immobilization of proteins in quenched spherical polyelectrolyte brushes as observed by fluorescence spectroscopy and small angle X‐ray scattering. Issue 23 (2nd October 2018) - Ye, Zhishuang; Li, Li; Zhao, Fang; Han, Haoya; Tian, Yuchuan; Wang, Yunwei; Yang, Qingsong; Fan, Wenting; Guo, Xuhong
ABSTRACT: The immobilization of lysozymes (pI = 11) onto anionic spherical polyelectrolyte brushes (SPB) which consist of a solid polystyrene core and a densely grafted poly(styrene sulfonate) (PSS) shell was systematically studied by fluorescence spectroscopy and small angle X‐ray scattering. Results show that the capture of lysozyme by PSS brush is a dynamic process, which involves a quick agglomeration stage and a slow rearrangement one. And lysozyme inclines to immobilize in the inner layer of the brush, and saturation of lysozyme adsorption onto the SPB is gradually reached as the protein concentration increases, proceeding from the inside to the outside of the brush layers. As increasing the pH and ionic strength, the lysozyme previously adsorbed will be partially released and migrate from the inner to the outer layer of SPB. Last competitive adsorption tests between lysozyme and BSA or β‐glucosidase were performed, indicating that besides electrostatic interaction counterion release force also plays an important role in protein adsorption. SPB was proved to be ideal candidate for controllable immobilization of protein, which can be extended into various applications, such as drug delivery and protein separation. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1577–1588 Abstract : Immobilization of proteins onto anionic spherical polyelectrolyte brushes can be controlled by tuning pH and ionic strength or injecting other kinds of proteins as revealed by fluorescence spectroscopy and small angle X‐ray scattering.